Short-Chain Fatty Acids Promote Immunotherapy by Modulating Immune Regulatory Property in B Cells - Cai-Jie Zhou; Bai-Ling Xie; Hai-Yang Han; Yin Wang; Yong-Hua Wang; Jing-Yi Hong; Yi-Xia Wei; Zhi-Gang Liu; Yan Feng; Gui Yang; Ping-Chang Yang (Journal of Immunology Research)
The dysfunction of regulatory B cells (Breg) may result in immune inflammation such as allergic rhinitis (AR); the underlying mechanism is not fully understood yet. Short-chain fatty acids, such as propionic acid (PA), have immune regulatory functions. This study is aimed at testing a hypothesis that modulates PA production alleviating airway allergy through maintaining Breg functions. B cells were isolated from the blood obtained from AR patients and healthy control (HC) subjects. The stabilization of IL-10 mRNA in B cells was tested with RT-qPCR. An AR mouse model was developed to test the role of PA in stabilizing the IL-10 expression in B cells. We found that the serum PA levels were negatively correlated with the serum Th2 cytokine levels in AR patients. Serum PA levels were positively associated with peripheral CD5+ B cell frequency in AR patients; the CD5+ B cells were also IL-10+. The spontaneous IL-10 mRNA decay was observed in B cells, which was prevented by the presence of PA through activating GPR43. PA counteracted the effects of Tristetraprolin (TTP) on inducing IL-10 mRNA decay in B cells through the AKT/T-bet/granzyme B pathway. Administration of Yupinfeng San, a Chinese traditional medical formula, or indole-3-PA, induced PA production by intestinal bacteria to stabilize the IL-10 expression in B cells, which promoted the allergen specific immunotherapy, and efficiently alleviated experimental AR. In summary, the data show that CD5+ B cells produce IL-10. The serum lower PA levels are associated with the lower frequency of CD5+ B cells in AR patients. Administration with Yupinfeng San or indole-3-PA can improve Breg functions and alleviate experimental AR.